VALIDITAS DAN RELIABILITAS INSTRUMEN STRESS AKADEMIK - Dina Rahmawati Hapsyah; Herdi Herdi; Wirda Hanim (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to measure the validity and reliability of the academic stress instrument developed by Sun, Dunne, & Hou (2011). This study uses a quantitative approach. The sampling technique uses the probability sampling method, namely cluster random sampling. The population in this study were students at the elementary, junior high school, senior high school,vocational school, and students with an age range of 12-19 years. The academic stress instrument has 16 favorable statement items. This scale uses a Likert scale model which has 5 alternative answers. The five alternative answers are Strongly Disagree (STS), Disagree (TS), Enough, Agree (S), Strongly Agree (SS). The results showed that 16 items were declared valid with an r count > 0.195 and an alpha reliability of 0.036.